The basis for a territorial and environmental arrangement of La Oroya - Junin - Peru - Capcha Rosales, A. (2006)
This study focuses on the production of a geotechnical map and a landslide hazard map in La Oroya district (Junín region in Perú), as a basis for land use planning. The method applied regards the analysis of the physical environment with a Geographic Information System (GIS) with layer (spatially referenced database) algebra. The results obtained show that this kind of maps represent a start point for land use and environmental planning, as they provide a reliable overview of where to carry out further studies (e.g. environment of Curipata) and which are the main advantages and disadvantages of the territory regarding geotechnics and landslides (the major natural hazard observed in the study area). The logical next study to carry out in the area after this survey should focus on obtaining maps of the other natural hazards that have been observed in the region (seismic and flood hazard maps), allowing to start examining other aspects and their relation with the natural environment, which is the basis for land use planning.